Astyanax douradilho, a new characid fish from the rio Tramandaí system, southern Brazil (Characiformes: Characidae) - Bertaco, Vinicius A. (Zootaxa, 2014)
Astyanax douradilho, new species, is described from the rio Tramandaí system, coastal drainage of Rio Grande do Sul State, Brazil. The new species is distinguished from its congeners by possessing 37–39 perforated scales along the lateral line, 3–5 maxillary tricuspid teeth, 22–24 branched anal-fin rays, absence of a conspicuous dark stripe from humeral region to caudal peduncle, two vertically elongated humeral spots, head length (26.0–29.9% of standard length), upper jaw length (43.8–50.6% of head length), and snout length (23.0–28.6% of HL).